2010
DOI: 10.3138/physio.62.3.180
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Treatment Techniques to Augment the Impact of Physiotherapy Interventions for Low Back Pain

Abstract: Purpose: The present study examined the profile of physical and psychosocial changes that occur in physiotherapy intervention when patients also participate in a psychosocial intervention. The psychosocial intervention, delivered by physiotherapists, was designed to target catastrophic thinking, fear of pain, perceived disability, and depression. Methods: The study sample consisted of 48 individuals referred for the rehabilitation treatment of disabling back pain. Half the sample was enrolled in a physiotherap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 35 publications
2
34
0
4
Order By: Relevance
“…2,55,59 Previous research also suggests that physical therapists can effectively use these interventions to help improve their patients' outcomes. 27,40,54 Although there has yet to be any physical therapy research that has specifically evaluated the impact of such psychosocial interventions on a sample of patients with depressive symptoms, results from a recent study by Sullivan and Adams 54 suggest their benefit. This study showed that when physical therapists added a psychosocial dimension to their traditional treatment, their patients experienced, on average, an additional 51% reduction in their symptoms of depression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,55,59 Previous research also suggests that physical therapists can effectively use these interventions to help improve their patients' outcomes. 27,40,54 Although there has yet to be any physical therapy research that has specifically evaluated the impact of such psychosocial interventions on a sample of patients with depressive symptoms, results from a recent study by Sullivan and Adams 54 suggest their benefit. This study showed that when physical therapists added a psychosocial dimension to their traditional treatment, their patients experienced, on average, an additional 51% reduction in their symptoms of depression.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, results from previous studies suggest that, for some patients, symptoms of depression can improve over the course of physical therapy treatment. 51,54 Thus, referral of patients whose symptoms would have resolved without the intervention of a mental health expert may prove to be an inefficient use of resources. Without additional research exploring the management of patients with depressive symptoms, physical therapists may be at a loss to decide when to proceed with treatment as usual or when additional interventions are warranted.…”
Section: T T Conclusion: For Many Patients Depressivementioning
confidence: 99%
“…Another possible explanation is that these previous studies were conducted in European countries, where most biopsychosocial theories/treatments have been developed and where the incorporation of the biopsychosocial model is stronger among healthcare providers 34 (e.g., cognitivebehavioral principles are fully integrated into physical therapy management of patients with low back pain [34][35][36][37] ).…”
Section: Discussionmentioning
confidence: 99%
“…The approach used in PGAP-Tel (and PGAP) to reduce catastrophizing includes education, the use of disclosure and validation techniques, thought monitoring/re-appraisal, goal setting, and activity participation. In previous research, these techniques have been shown to be effective in reducing catastrophic thinking [33,36,43]. It is not clear why these techniques are less effective when used telephonically as opposed to face-toface.…”
Section: Original Researchmentioning
confidence: 99%